Association between vitiligo and risk of suicide and suicidal ideation: systematic review and meta-analysis - Kevin Phan; Stephen Shumack; Monisha Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: Vitiligo is an autoimmune skin disorder characterized by patches of depigmentation due to loss of melanocytes. Vitiligo is associated with significant psychosocial burden, with prior studies showing links with psychiatric comorbidities such as depression. Few studies have evaluated the relationship between vitiligo and suicidal ideation and suicide attempts. We aimed to investigate the underlying prevalence and risk of suicidal ideation or suicide attempts among patients with vitiligo. Materials and Methods: A systematic search of PubMed, MEDLINE, Embase, and the Cochrane Library was conducted. Cross‐sectional, case-control or cohort studies that assessed the prevalence of suicidal ideation or suicide attempts among patients with vitiligo were included. DerSimonian and Laird random‐effects models were utilized to calculate the pooled prevalence and odds ratios. Results: From systematic review, we identified seven studies included for analysis. A total of 12,043 vitiligo cases were compared with 87,053,333 controls. The pooled proportion of suicidal ideation in vitiligo was 15.2% compared to 2.0% in the control group (P < 0.001). The proportion of suicide attempts/suicides was also higher for vitiligo compared to controls (3.2% vs. 2.1%, P < 0.001). Moderate‐to‐high heterogeneity was observed between the studies. Conclusion: Our data further provide evidence of the significant impact vitiligo has on self-esteem and psychological burden. Patients with vitiligo were significantly more likely to have suicidal ideation. Clinicians should actively evaluate patients with vitiligo for signs/symptoms of suicidal ideation and provide appropriate referrals to manage their psychiatric symptoms accordingly.